Making Universities Matter Collaboration, Engagement, Impact - Mattsson, Pauline; Perez Vico, Eugenia; Salö, Linus (Innovation, Technology, and Knowledge Management, 2024)
In an era of rapid change and increasing societal demands, the role of universities as knowledge producers and catalysts for change has come under scrutiny. This open access book offers a fresh perspective on the significance of universities in society, shedding light on how their knowledge can truly matter beyond academia. Drawing upon insightful inquiries from both the Swedish and international contexts, this volume delves into the multifaceted interactions between universities and various knowledge users, emphasizing the need for scholars to reflect on how their knowledge can become useful and applicable to wider society. Organized into three compelling themes, collaboration, engagement, and impact, this book explores the concept of "mattering". Together and jointly, they point at the fluid movement of scholars and scholarly knowledge across academic, political, and public spaces, and the intentional actions of scientists to leverage their expertise for real-world impact. Essential reading for social science and humanities scholars, university management professionals, and individuals keen on a critical understanding of the evolving role of universities, this volume offers a comprehensive examination of how universities have mattered, continue to matter, and can shape the future.